Aspectos histomorfológicos e imunohistoquimicos da adrenal de ratas pinealectomizadas e tratadas com melatonina - Fuchs, Luiz Fernando Portugal [UNIFESP] (2010)
Introduction: The pineal gland is the modulator of mammal’s reproduction, it has some influence in gonads and in the estrous cycle thru hipotalamus-ovary-adrenal axis. Objectives: The objective of this study is to analyze the histomorphology and imunnohistochemical of the pinealectomized and treated with melatonin female rat’s adrenals. Material and methods: Forty adult female rats were divided in 4 groups of 10 animals each. GI – no surgery intervention, with vehicle administration; GII – falsely pinealectomized with vehicle administration; GIII – pinealectomized with vehicle administration; GIV – pinealectomized with melatonin administration (10μg/animal) during the night. After 60 days of experiment, all animals where anesthetized, and the adrenal removed and fixed in 10% formaldehyde. After histological processing to be embedded in paraffin, some slides were stained by H.E. and others submitted to imunnohistochemical to detection of Caspase-3 clivated (apoptosis) and vascular endothelial growth factor VEGF. The obtained data were submitted to statistics (P<0,05). Results: Morphologically, there weren’t modifications in the glomerulosa zone in any of the studied groups. In GIII there was a slightly increase of the adrenal size and the reticularis zone presented with volumous nucleus rich in eurocromatin. In GIV those findings from the previous group had been reversed. In immunohistochemical, there was a decrease in apoptosis detected by Caspase-3 in the GIII (fasciculate zone) and GIV (fasciculata and reticularis zone). VEGF had its smaller reaction in the reticularis zone in all groups, the only difference being the fasciculate zone in GIII, which had shown an increase of the reaction. Conclusion: our data suggests that exogenous melatonin can reverse the effects of pinealectomy.